Gastric metastasis before diagnosis of primary invasive lobular breast carcinoma: a rare case presentation from Pakistan. Issue 9 (21st October 2021) - Ali, Mashhood; Aziz, Shahid; Ahmad, Imran; Saadia, Aiza; Zahra, Rabaab; May, Felicity E. B.; Pritchard, David Mark; Rasheed, Faisal
ABSTRACT: Metastatic spread of invasive lobular breast carcinoma to stomach is rare especially before diagnosis of primary breast cancer. Incorrect diagnosis might result in delay of appropriate treatment for breast cancer. Recognition of this possibility enables better clinical management. A 62-year-old female presented with upper gastrointestinal symptoms and weight loss and was referred to a gastroenterologist for investigation. At the time of initial diagnosis of stomach cancer, patient was asymptomatic for breast cancer. Multiple gastric biopsies taken showed features suspicious of metastatic breast cancer. Consequently, the initial provisional diagnosis of stomach cancer changed into metastatic invasive lobular breast carcinoma. These findings were corroborated radiologically. The patient was treated with letrozole and zoledronic acid as first-line therapy for one year. Residual metastatic breast cancer was present in the gastric mucosa. The patient was treated with endocrine therapy containing ribociclib and treatment was ineffective confirmed by PET-CT scan. But her symptoms have resolved completely despite her presentation with stage IV. We present rare case of initial presentation of gastric metastasis before diagnosis of a primary invasive lobular breast carcinoma. Correct diagnosis and appropriate treatment were accomplished through initial clinical suspicion, accurate histological examination, and endoscopy together with analysis of disease-specific biomarkers.